2021
DOI: 10.1084/jem.20211523
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PLD2 in adipocytes augments adaptive thermogenesis by improving mitochondrial quality and quantity in mice

Abstract: Phospholipase D (PLD)2 via its enzymatic activity regulates cell proliferation and migration and thus is implicated in cancer. However, the role of PLD2 in obesity and type 2 diabetes has not previously been investigated. Here, we show that during diet-induced thermogenesis and obesity, levels of PLD2 but not PLD1 in adipose tissue are inversely related with uncoupling protein 1, a key thermogenic protein. We demonstrate that the thermogenic program in adipose tissue is significantly augmented in mice with adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…This inhibitor was able to restore to control levels the median mitochondria diameter and the number of ridges per mitochondrion in ORF3a‐A549 cells (Figure 8A–C). These results agree with other studies, which showed an improvement in mitochondrial quality and quantity after PLD pharmacoinhibition 62 . Integration of transcriptomics data into treatment‐specific GSMM to simulate the effect of CAY10594 inhibitor on ORF3a‐A549 cells metabolic flux distribution, showed that alterations on the major lipid superfamilies induced by ORF3a are partially reverted by the PLD2 inhibitor (Figure 8D, bottom panel).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This inhibitor was able to restore to control levels the median mitochondria diameter and the number of ridges per mitochondrion in ORF3a‐A549 cells (Figure 8A–C). These results agree with other studies, which showed an improvement in mitochondrial quality and quantity after PLD pharmacoinhibition 62 . Integration of transcriptomics data into treatment‐specific GSMM to simulate the effect of CAY10594 inhibitor on ORF3a‐A549 cells metabolic flux distribution, showed that alterations on the major lipid superfamilies induced by ORF3a are partially reverted by the PLD2 inhibitor (Figure 8D, bottom panel).…”
Section: Resultssupporting
confidence: 91%
“…75,76 In our study, qMTA simulations predicted phospholipase D2 (PLD2) and phospholipase C β-1 (PLCB1) as the best targets for reverting the metabolic phenotype induced by ORF3a in A549 cells. Of note, it is reported that PLD2 augments adaptative thermogenesis by improving mitochondrial quality and quantity, 62 and phosphatidic acid, the catalytic product of PLD2, has been described as essential for SARS-CoV-2 replication. 77 as previously described, 62 we have showed that PLD inhibitor treatment was able to revert altered mitochondria morphology in ORF3a-A549 cells, and restore control cells metabolic phenotype, validating the gene knock downs (KDs) simulation obtained by our model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been demonstrated that PLD2 has an inverse relationship with UCP1, which is achieved by regulating the number of mitochondria through p62. These results suggest that PLD2 participates in the browning of white adipocytes [ 30 , 32 ]. In this study, we investigated the effect of PLD2 on beige adipocyte properties using a pharmacological inhibitor and knockdown system.…”
Section: Discussionmentioning
confidence: 99%